1997
DOI: 10.1002/jlac.199719970107
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Benzimidazole Cyanine Dyes, Their Spectroscopy and Their Performance in Photographic Emulsions

Abstract: The multi-step synthesis of two benzimidazole trimethine cyanines as possible green sensitizing dyes (Gs3-1, Gs3-2) is reported. Compounds were characterized from UV-Vis, mass spectroscopic and NMR data. The charge density distributions of the two compounds, calculated using the semi-empirical MOPAC 93 package, are in agreement with assignments in NMR spectroscopy. Sensitizing properties of the cyanine dyes were evaluated in actual photographic T-grain emulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…For the dye formation/ release step we found that 30 min at room temperature in 1:9 DIEA/pyridine was sufficient to completely react 0.3 equiv of lepidinium salt 4 . This contrasts with the 45 min at reflux in 1:5 DIEA/pyridine used by Peng et al After being washed twice with water, the product 5 was obtained in 89% purity and 79% crude yield.
1 Synthetic Route to Unsymmetrical Cyanine Dyes a a (i) (EtO) 3 CH, EtOH, 80 °C, 2 h; (ii) DIEA, DCM, rt, 4 h; (iii) DIEA, pyridine, rt, 30 min.
…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…For the dye formation/ release step we found that 30 min at room temperature in 1:9 DIEA/pyridine was sufficient to completely react 0.3 equiv of lepidinium salt 4 . This contrasts with the 45 min at reflux in 1:5 DIEA/pyridine used by Peng et al After being washed twice with water, the product 5 was obtained in 89% purity and 79% crude yield.
1 Synthetic Route to Unsymmetrical Cyanine Dyes a a (i) (EtO) 3 CH, EtOH, 80 °C, 2 h; (ii) DIEA, DCM, rt, 4 h; (iii) DIEA, pyridine, rt, 30 min.
…”
mentioning
confidence: 76%
“…Simple washing is adequate to remove residual aniline and amidine. We envisaged activating the hemicyanine carbon toward a second nucleophilic attack by N - sulfonylation as demonstrated in solution by Peng et al, rather than the more traditional acylation step. This is consistent with the findings of Brooker et al that the less available the nitrogen lone pair is for delocalization, the more reactive the hemicyanine derivative is to nucleophiles .…”
mentioning
confidence: 99%
“…The immobilization of the hemicyanine onto the resin has the dual function of activating the hemicyanine and of facilitating the removal of the major byproducts. The hemicyanine intermediates are relatively unreactive at room temperature but can be activated by functionalizing the nitrogen with an electron-withdrawing group like by acetylation or sulfonylation [43,44]. In a similar manner, the reaction of the hemicyanine with a sulfonyl chloride polymer-bound resin not only activates the substrate but also allows the removal of the undesired byproducts, mainly the symmetrical CD, by simple washing the resin with compatible solvents.…”
Section: Solid-phase Synthesis Of Asymmetrical Cyaninesmentioning
confidence: 99%
“…In our previously published strategy, hemicyanine 7 was synthesized from the reaction of heterocycle 2 with amidine 6 . Hemicyanine intermediates such as 7 are relatively unreactive at room temperature but can be activated by functionalization of the aniline nitrogen with an electron-withdrawing group, for example, by acetylation or sulfonylation. , By reaction of hemicyanine 7 with sulfonyl chloride polystyrene, we demonstrated its activation via concurrent immobilization onto the solid phase (Scheme ).
2 Catch-and-Release Synthesis of Trimethine Cyanine Dye a a Reagents and conditions: (a) 2 , EtOH, triethylorthoformate, reflux; (b) dichloromethane (DCM), diisopropylethylamine (DIEA), polystyrene (PS)-SO 2 Cl; (c) 4 , pyridine, DIEA.
…”
Section: Introductionmentioning
confidence: 98%